All That Remains: Typhoons and Trauma in Three Philippine Novels in English - Bichara, Alexandra (Journal of Ecohumanism, 2024)
In November 2013, one of the most powerful typhoons ever recorded ravaged the Visayas region of the Philippines. Typhoon Haiyan, locally known as Typhoon Yolanda, caused the deaths of over 6,500 Filipinos. Years later, many are still missing. The devastation caused by typhoons such as Typhoon Haiyan is not new to the Philippines, considering the country encounters around 20 tropical cyclones every year. It is not surprising, then, that natural disasters figure heavily in Philippine literature. This is evident in three Philippine novels in English: Broken Islands (2019) by Criselda Yabes, Remains (2019) by Daryll Delgado, and Tiempo Muerto (2019) by Caroline Hau. Using Sigmund Freud’s concept of â€œremembering, repeating, and working-through,â€ this study analyzes the three novels as patients in recovery after the trauma of natural disaster. These three novels are then connected to Ernest Renanâ€™s concept of nationhood, Marianne Hirsch’s notion of postmemory, as well as Pierre Nora’s concept of lieux de memoire in order to illustrate the importance of disaster narratives in the creation and preservation of a nation’s identity.